Durian seed meal for commercial layers: performance, nutrient retention and egg quality - Mangisah, I.; Ismadi, V. D. Y. B.; Sukamto, B.; Wahyono, F.; sugiharto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This study was conducted to evaluate diets containing durian (Durio zibethinus Murr) seed meal (DSM) on the performance, nutrient retention and egg qualities of commercial layers. A total of 120 fifty two -week-old laying hens were distributed according to a completely randomized design in four treatments and five replications with six birds each. The treatments consisted of different levels of durian seed meals (control, 3% DSM, 6% DSM, and 9% DSM). Feeding diets containing durian seed meal had no significant effect (p > 0.05) on the feed consumption of laying hens at 58 wk of age. Inclusion of up to 6% DSM in formulated layer diets did not reduce egg production and nutrient digestibility, but reduced egg weight. No differences (p>0.05) were observed in egg calcium content, egg calcium mass, and yolk color score fed diets containing DSM. This study suggests that DSM could be incorporated up to 6% in laying hen diets without adverse effect on production performance, nutrient retention and egg qualities.